'There is no formula for life and career': A commentary on perspectives and experiences of early career quantitative human geographers. Issue 1 (26th December 2022) - Ballantyne, Patrick; Sanderson, Rachael K.; Davies, Alec; Houlden, Victoria; MacLachlan, Andrew; Owen, Gwilym; Robinson, Caitlin; Shin, Hyesop; Wartmann, Flurina M.; Wilkin, Joanna; Williams, Isabel
Abstract: Early career researchers (ECRs) encounter distinctive opportunities (and challenges) within the neoliberal academy. In this commentary, we reflect on issues common to ECR experiences in quantitative human geography. Our discussion is inspired by and develops conversations from a panel at the Royal Geographical Society‐Institute of British Geographers (RGS‐IBG) postgraduate forum, with panellists from across the subfield. While many aspects of the ECR experience transcend sub‐disciplinary boundaries, the quantitative subfield presents unique dynamics for ECRs to navigate. ECRs in quantitative geography are steeped in 'data science', which changes relations between academia and industry, with the growth of our field increasing the size and the scope of what ECRs might be expected to know and do. Bringing together reflections from the panel, we highlight the variation in pathways experienced by ECRs, reflecting on opportunities, uncertainties, and mentorship, in the hope of offering insights and advice for prospective and current ECRs and their mentors. This commentary reflects on the perspectives and experiences of early career quantitative human geographers, placing significant emphasis on opportunities, uncertainty, and mentorship, and the overall diversity of pathways available to other early career quantitative human geographers. Short Abstract: This commentary reflects on the perspectives and experiences of early career quantitative human geographers, placing significant emphasis on opportunities, uncertainty and mentorship, and the overall diversity of pathways available to other early career quantitative human geographers.